Distinct Roles for Bacterial and Fungal Communities During the Curing of Vanilla - Xu, Fei; Chen, Yonggan; Cai, Yingying; Gu, Fenglin; An, Kejing (Frontiers in Microbiology, 2020)
Vanilla produces aroma after curing. There are a few reports about the possible involvement of microorganisms during the curing process. Microbial community was analyzed by pyrosequencing to explore distinct roles. Alpha diversity analysis indicated that the abundance and diversity of microorganisms did not increase regularly as the curing progressed. PCoA analysis showed the microbial community structure of fresh vanilla beans and conditioning vanilla beans were significantly different from those of vanilla beans of other curing stages. Bacillus and Aspergillus are the dominant genus during curing process. Correlation analysis indicated that bacteria richness was closely related to vanillin formation and bacteria and fungi structure was also closely related to it. The study was conducive to revealing the formation of flavor components and the biosynthesis pathway of vanillin. Furthermore, it proposed the possible curing methods of regulating the structure of microbial community to increase vanillin formation.